2009
DOI: 10.1007/s12542-009-0025-5
|View full text |Cite
|
Sign up to set email alerts
|

Oligocene and Early Miocene gastropods from Kutch (NW India) document an early biogeographic switch from Western Tethys to Indo-Pacific

Abstract: Shallow marine gastropod assemblages from Chattian, Aquitanian and Burdigalian sections in the Indian Kutch Basin are described. They provide insight into the composition and biogeographic relations of the gastropod assemblages at this junction between the Western Tethys and Proto-Indo-Pacific Ocean. For the first time, an improved biostratigraphy allows a clear separation of the assemblages, especially for the hitherto undifferentiated Early Miocene faunas. Throughout the Oligocene, about one-third of the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 48 publications
6
55
2
Order By: Relevance
“…Therefore we suggest that, prior to approximately 14 Ma, a relatively deep seaway connected the Indian Ocean and the proto-Mediterranean, allowing the production of TISW. Moreover, the termination of TISW production during the MMCT (Woodruff and Savin, 1989;Wright et al, 1992;Kennett, 1994, 1995) suggests a middle Miocene age for the final closure of the Tethys seaway, which is consistent with oceanic palaeontological data (Rögl, 1999;Harzhauser et al, , 2009Reuter et al, 2009). Our results are in disagreement with the study of Hüs-ing et al (2009), who suggested that a connection between the Mediterranean Sea and the Indian Ocean still existed at 11 Ma.…”
Section: Timing Of the Eastern Tethys Seaway Closurecontrasting
confidence: 60%
See 3 more Smart Citations
“…Therefore we suggest that, prior to approximately 14 Ma, a relatively deep seaway connected the Indian Ocean and the proto-Mediterranean, allowing the production of TISW. Moreover, the termination of TISW production during the MMCT (Woodruff and Savin, 1989;Wright et al, 1992;Kennett, 1994, 1995) suggests a middle Miocene age for the final closure of the Tethys seaway, which is consistent with oceanic palaeontological data (Rögl, 1999;Harzhauser et al, , 2009Reuter et al, 2009). Our results are in disagreement with the study of Hüs-ing et al (2009), who suggested that a connection between the Mediterranean Sea and the Indian Ocean still existed at 11 Ma.…”
Section: Timing Of the Eastern Tethys Seaway Closurecontrasting
confidence: 60%
“…During the Cenozoic, the collision between the AfroArabian and Eurasian plates closed the Tethys seaway which connected the proto-Mediterranean Basin and the Indian Ocean (Rögl, 1999;Harzhauser et al, , 2009). The timing of this seaway closure is still under debate.…”
Section: N Hamon Et Al: Tethys Seaway Closure and Middle Miocene CLmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyclones are one of the most devastating weather phenomena that affect tropical coasts (Henderson-Sellers et al, 1998). For this reason, attempts to relate trends in tropical cyclone intensity and frequency with global change have become a challenging subject in recent years (e.g.…”
Section: Introductionmentioning
confidence: 99%